Empowering MSME Employees: Quality of Work Life and Organizational Support : Memberdayakan Karyawan UMKM: Kualitas Kehidupan Kerja dan Dukungan Organisasi - Izzatunissa; Hidayah, Nur (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study investigates the association between quality of life at work (QWL), perceived organizational support (POS), and employee performance in Kota Magelang's micro, little, and medium-sized firm (MSME) sector. Through a questionnaire issued to 210 MSME employees, with a 100% response rate, the research explores the impact of QWL on both employee performance and POS, as well as the mediating role of POS in the relationship between QWL and employee performance. The findings show a good relationship between QWL and staff performance, as well as a positive influence of QWL on the point of sale. Furthermore, the study emphasizes the mediating role of POS in the relationship between QWL and employee performance. These findings highlight the necessity of improving QWL and POS within MSMEs to support increased employee performance, hence contributing to the economic development of Magelang's City MSME sector.